Fermented soybean meal in broiler diets exposed to stress induced by corticosterone: Effect on growth performance, gut health and immune response - Fakhreddin ABEDDARGAHI; Hassan DARMANI-KUHI; Mohammad ROOSTAIE-ALIMEHR; Seyed H. HOSSEINI-MOGHADDAM; Reza HASSAN-SAJEDI; Anahid HOSSEINI; Fatemeh MOHAMMADPOUR (Spanish Journal of Agricultural Research, 2023)
Aim of study: To investigate the effect of fermented soybean meal (FSBM) on responses of broiler chickens exposed to stress condition.